2010
DOI: 10.1099/jmm.0.017582-0
|View full text |Cite|
|
Sign up to set email alerts
|

Allelic variation in colonization factor CS6 of enterotoxigenic Escherichia coli isolated from patients with acute diarrhoea and controls

Abstract: Colonization factor antigens (CFAs) are important virulence factors in enterotoxigenic Escherichia coli (ETEC). Using a multiplex PCR and RT-PCR, this study tested the presence of common colonization factor-encoding genes and their expression in 50 ETEC strains isolated from stool specimens. The samples were from patients (children) with acute diarrhoea (cases) admitted to the Infectious Disease Hospital (Kolkata, India) and from normal children (controls) under 5 years of age from the community. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Our previous studies also demonstrated that CS6 is one of the most prevalent CFs among the clinical ETEC isolates obtained from hospitalized diarrhoeal patients (Ghosal et al, 2007;Sabui et al, 2010). Based on the high prevalence of CS6 positive ETEC, CS6 has been proposed as an important vaccine candidate (de Lorimier et al, 2003;Ghosal et al, 2007;Sabui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies also demonstrated that CS6 is one of the most prevalent CFs among the clinical ETEC isolates obtained from hospitalized diarrhoeal patients (Ghosal et al, 2007;Sabui et al, 2010). Based on the high prevalence of CS6 positive ETEC, CS6 has been proposed as an important vaccine candidate (de Lorimier et al, 2003;Ghosal et al, 2007;Sabui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The structural genes of CS6 are cssA and cssB, which exhibit variation in different CS6-expressing ETEC isolates (16,20). Recently, we documented that cssA has three alleles (AI, AII, and AIII) and cssB has two alleles (BI and BII).…”
mentioning
confidence: 99%
“…Due to the increase in the incidence of ETEC-mediated diarrheal disease, considerable attention has been paid to the development of simple, sensitive, and less expensive molecular methods for rapid identification of the pathogen. Currently, CFAs are detected by conventional PCR assay, replacing the conventional immunological tests (7,12,13,16,17).The CS6 operon is composed of four genes, cssA, cssB, cssC, and cssD. The structural genes of CS6 are cssA and cssB, which exhibit variation in different CS6-expressing ETEC isolates (16,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations